The effect of soil tillage and nutrient supply on maize yield based on multi-year experimental results - Ragán, Péter; Rátonyi, Tamás; Fejér, Péter; Harsányi, Endre; Balláné Kovács, Andrea; Gumisiriya, Costa; Nagy, János; Sojnóczki, István; Tamás, András (Precision Crop Production, 2025)
To optimize maize (Zea mays) yield, soil tillage and nutrient supply play a key role. The application of appropriate soil tillage techniques and the precise application of nutrients can contribute to increasing yield, maintaining plant health, and developing sustainable agricultural practices. The aim of the study was to analyse the long-term yield performance of maize hybrids under different nutrient supply levels and basic tillage methods. According to the repeated measurement model, soil tillage, fertilization, and crop year had a significant (p